A delamination failure criterion considering the effects of through-thickness compression on the interlaminar shear failure of composite laminates. (1st June 2020) - Chen, Xiangming; Sun, Xiasheng; Chen, Puhui; Chai, Yanan
Abstract: Through-thickness compressive stress of composite laminates can inhibit the interlaminar shear failure which has been proved by experiments. However, common delamination damage initiation criterion cannot well describe this mechanism. For this issue, in this article, based on the insight of the failure mechanism, an interlaminar failure function is constructed at first. Then, a delamination failure criterion considering the effect of through-thickness compression on interlaminar shear failure is established based on logical deductions from a polynomial expansion of the failure function. In the criterion, a constant coefficient with physical meaning is used to describe the effect of through-thickness compression on the interlaminar shear failure, and the estimation method of the coefficient is also given in this study. Here, this failure criterion can be considered as a general form to describe the delamination between laminae, by defining different coefficient, it can be converted to other criteria such as the conventional secondary stress failure criterion or the Christensen failure criterion. Finally, by comparing the numerical calculation and experimental results, the delamination failure criterion proposed in this study exhibited a good prediction ability for the interlaminar damage under different loading conditions.